PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL INKUIRI UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS DAN PENGUASAAN KONSEP SISWA SMP - Rinarta, I Nyoman; Yuanita, Leny; Widodo, Wahono (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The research aims to develop inquiry learning materials to facilitate science process skills and science concept mastery the junior high school students in energy and works matter. The research was conducted through two phase that is development phase by using 4-D models and implementation phase using one group pretest-posttest design. Data collection methods used test and observation, while the data analysis techniques using inferential parametric, quantitative descriptive, and qualitative descriptive. The result were obtained: the devices that have been developed are generally categorized as well; RPP performing well; activity is the dominant doing observation; The results also showed that mean of N-gain score mastery of concepts in high category; science process skills in high category; students mastery of the concept after learning improving; students responses to learning a positive model of inquiry. Based on the research results, it can be concluded that the develop inquiry learning materials effective that can be applied in learning activities in grade VIII of SMP.